2012
DOI: 10.4321/s0004-05922012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Whole hatchery waste meal as alternative protein and calcium sources in broiler diets

Abstract: SUMMARYA study was conducted in which processed whole hatchery waste meal (WHWM) replaced fish meal (FM), protein for protein, in broiler diets at 0, 10, 20 and 30% levels. There were 45 birds per treatment and 15 birds per replicate. The feeding trial which lasted for 42 days, was carried out at the Poultry Unit, Agricultural Research Council, Glen. Chemical analysis of the two test ingredients indicated that WHWM had higher contents of ash (18.12%) and ether extract (23.94%). However, crude protein content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…The result agreed with that of Abiola et al (2012), they concluded that there were no significant differences in the relative weight of abdominal fat, when they replaced fish meal with poultry hatching powder in broiler diets. However, Sahraei et al (2012), observed a significant differences (P<0.05) in the relative weight of abdominal fat between a control and treatment of the slaughterhouse wastes broiler diets.…”
Section: Resultssupporting
confidence: 83%
“…The result agreed with that of Abiola et al (2012), they concluded that there were no significant differences in the relative weight of abdominal fat, when they replaced fish meal with poultry hatching powder in broiler diets. However, Sahraei et al (2012), observed a significant differences (P<0.05) in the relative weight of abdominal fat between a control and treatment of the slaughterhouse wastes broiler diets.…”
Section: Resultssupporting
confidence: 83%
“…In a related study, while Abiola et al (2012) observed that ADG was not signi cantly (p > 0.05) affected by the inclusion of varying levels of HWM in diets fed to laying hens Orozco-Hernandez et al (2003) reported that rations containing HWM elicited a better performance in terms of weight gain and feed e ciency in broilers, fed up to 12% HWM than in others fed similar of sh meal. Abiola (2010) on the other hand indicated that using HWM in pig diets resulted in a decrease in average daily live weight gain whereas Abiola et al (2012) indicated that pigs could generally be fed HWM in place of FM without affecting growth performances and survivability.…”
Section: Discussionmentioning
confidence: 99%
“…The HBPs contain high amounts of energy, protein, and calcium ( Ca ) although variations in nutritional compositions are relatively high, indicating that HBPs can be a potential ingredient in animal diets ( Abiola et al, 2012 ; Sung et al, 2020 ; Choi et al, 2021 ). However, the detailed information regarding nutritional values for HBPs in animal diets is largely lacking.…”
Section: Introductionmentioning
confidence: 99%